Understanding the role of leadership on a resources firm’s culture of belonging and its impact on future Environmental, Societal and Governance (ESG) performance: Implications for leaders, investors and regulators. - Hewitson, Matthew (Curtin University, 2023)
To deepen an understanding of the significance of a sense of belonging in resources firms, the effect of sense of belonging and its influence on a firm’s ESG performance is examined with reference to the CEO letter contained within the annual report. Analysis performed on a sample of ASX listed firms from the resources industry using quantitative research methods to explore language in the CEO letter contained in the annual report, revealed a significantly positive relationship between sense of belonging and future environmental performance.